Academic Instincts. - Garber, Marjorie (Princeton University Press, 2003)
In this lively and provocative book, cultural critic Marjorie Garber, who has written on topics as different as Shakespeare, dogs, cross-dressing, and real estate, explores the pleasures and pitfalls of the academic life. Academic Instincts discusses three of the perennial issues that have surfaced in recent debates about the humanities: the relation between "amateurs" and "professionals," the relation between one academic discipline and another, and the relation between "jargon" and "plain language." Rather than merely taking sides, the book explores the ways in which such debates are essenti